2004
DOI: 10.1055/s-2004-822364
|View full text |Cite
|
Sign up to set email alerts
|

Functionalized BINOL Derivatives as Ligands for Enantioselectively Catalyzed Aldol Additions: Highly Enantioselective Synthesis of Chiral β-Hydroxy Thioesters

Abstract: A series of 3,3¢-disubstituted and 6,6¢-disubstituted BINOL derivatives was synthesized and examined in typical titanium(IV) promoted aldol reactions. The model reaction of S-ketene silyl acetal 13 and aldehydes 12a and 12b revealed that 6,6¢-dibromo-BINOL derivative (R)-6 is the ligand of choice for these transformations. Up to 97% yield with excellent enantioselectivity (ee > 97%) could be achieved. Scope and limitations were demonstrated using a series of aldehydes as substrates, which were generally transf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…The ethoxy-groups were removed after the iodination in positions 3,3 0 with BBr 3 in CH 2 Cl 2 to yield compound (R)-18 15 quantitatively. Sonogashira-coupling with trimethylsilyl acetylene and subsequent cleavage of the TMS-groups under basic conditions gave bisalkynes (R)-19 16 and (R)-20 17 in quantitative yields, respectively. Although quantitative consumption of the alkyne was observed, unfortunately, no product arising from the double benzannulation of (R)-20 and pentacarbonyl[methoxy(phenyl)carbene]chromium could be isolated after in situ oxidation with CAN.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ethoxy-groups were removed after the iodination in positions 3,3 0 with BBr 3 in CH 2 Cl 2 to yield compound (R)-18 15 quantitatively. Sonogashira-coupling with trimethylsilyl acetylene and subsequent cleavage of the TMS-groups under basic conditions gave bisalkynes (R)-19 16 and (R)-20 17 in quantitative yields, respectively. Although quantitative consumption of the alkyne was observed, unfortunately, no product arising from the double benzannulation of (R)-20 and pentacarbonyl[methoxy(phenyl)carbene]chromium could be isolated after in situ oxidation with CAN.…”
Section: Resultsmentioning
confidence: 99%
“…After removing the solvent under reduced pressure, the remaining residue was dried in vacuo to give compound 19 (0.34 g, 99%) as a white solid; the spectroscopic and chiroptical data were in agreement with those reported in the literature. 16 4.14. (R)-3,3 0 -Diethynyl-2,2 0 -dihydroxy-1,1 0 -binaphthyl, 20…”
Section: General Proceduresmentioning
confidence: 99%
“…416 A screening of different BINOL derivatives showed that varying the electronic properties of substitutents at the 6 position had a remarkable influence on the enantioselectivity and the chemical yield, with the best BINOL being the ligand 90ax, which could perform the aldol reaction in the absence of any additive with a wide scope of different functionalized aldehydes (for instance 57%, 92% for compound 307b). 417 However, substituents at the 3 position of ligands had a detrimental effect.…”
Section: Aldol-type Reactionsmentioning
confidence: 99%
“…The catalytic system worked best at 0°C by using 20 mol% of catalyst (Table 2, entry 2). The dibromobinaphthol ligand D 18 furnished moderate to good yields (23-84%) and the enantiomeric excess was consistently superior (≥96%; Table 2, entries 5-7). Best results were obtained running the reaction at 0°C: An excellent enantiomeric excess of 98% and 84% yield were obtained using 20 mol% of catalyst (Table 2, entry 6).…”
mentioning
confidence: 99%